Research on High Voltage Direct Current Power Supply System for Telecommunications - Li Lu; Shineng Lai; Wenbo Sun; Fuping Hou (Dianxin kexue)
The analysis was made for the nominal voltage selection and system design method which was based on energy efficiency prompt and power reliability increasing,these different goals to replace AC power system by DC power system,and these two direct current power supply system was introduced.It was compared that the reliability,the efficiency,the security and the input/output ratio which could prove the scientifically and large-scale application feasibility of 240V direct current power supply system.